If a polynomial function has a zero at 1, one of its factors is (x-1), since when

x-1=0

we know x=1.

So there are three factors of this polynomial. Write them beside each other to write the function in factored form: y = (x-1)(x-2)(x-5).

And start multiplying!

y = (x^{2}-3x+2)(x-5)

Then keep multiplying:

y = x^{3}-3x^{2}+2x-5x^{2}+15x-10

And combine like terms to get the final answer:

**y=x**^{3}**-8x**^{2}**+17x-10**

Note: the leading coefficient is already 1. If you wanted a different coefficient, you would just multiply each term by that number.

I hope this helps!

Have fun!